2020
DOI: 10.3389/fpsyg.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Temperament and School Adjustment in Spanish Children: A Person-Centered Approach

Abstract: The aim of this study was to examine from a person-centered approach the impact of temperament on academic achievement and sociometric status in a sample of 6-7-yearold Spanish children. To measure children's temperament in early childhood, parents were given TMCQ (Temperament in Middle Childhood Questionnaire), while sociometric status and academic achievement were requested for children's teachers. Using latent profile analysis (LPA) four temperament profiles were found. Children belonged to the "Negative/Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Temperament can influence a child’s functioning during school performance and therefore to some extent either enhance or limit the child’s performance. In mathematics, reading, or other school activities which require the child to calm down, concentrate on the task, and resist stimuli from the surroundings, temperament can be a very important factor ( Collings et al, 2017 ; Ato et al, 2020 ). Therefore, it can have a negative influence on the performance of a child who is functioning cognitively quite well, but is unable to concentrate, calm down, and detach him- or herself from disturbing stimuli from outside.…”
Section: Discussion and Possible Application In Practicementioning
confidence: 99%
“…Temperament can influence a child’s functioning during school performance and therefore to some extent either enhance or limit the child’s performance. In mathematics, reading, or other school activities which require the child to calm down, concentrate on the task, and resist stimuli from the surroundings, temperament can be a very important factor ( Collings et al, 2017 ; Ato et al, 2020 ). Therefore, it can have a negative influence on the performance of a child who is functioning cognitively quite well, but is unable to concentrate, calm down, and detach him- or herself from disturbing stimuli from outside.…”
Section: Discussion and Possible Application In Practicementioning
confidence: 99%
“…Thomas and Chess (1977) suggested that temperament is used to determine how a children will react to a situation, and how they express and control their emotions. Despite numerous studies (Ato et al, 2020;Bryce et al, 2018;Bush 2018) on temperament across various contexts, recent research (Thandevaraj, 2021) has directed its attention towards the impact of temperament on student engagement, particularly among students in primary school and the same interest is observed in Malaysia. The Rothbart model (2004) defines temperament as a set of individual differences in emotion, attention, and self-regulation processes.…”
Section: Temperamentmentioning
confidence: 99%
“…Our focus on the TMCQ, in particular, due to its importance for studies of development and psychopathology in middle childhood, the peak years of onset for common psychopathology and a critical period for child development (Shiner, 2021), and the shortage of validation studies of it. The TMCQ has been used for multiple studies of cognitive, personality, and neural development (Affrunti et al, 2014; Affrunti & Woodruff-Borden, 2015; Ato et al, 2020; Inuggi et al, 2014), as well as developmental psychopathology (Karalunas et al, 2019; Kotelnikova et al, 2015, 2017; Nigg et al, 2020; Rutter & Arnett, 2021). The TMCQ is designed to evaluate temperament in the regulation–reactivity model from ages 7 to 10, although there is evidence that such questionnaires can be used and are used outside their originally intended age ranges (Soto & John, 2014) and can be completed by adult raters or by self-report (Simonds & Rothbart, 2004, 2009).…”
Section: The Tmcqmentioning
confidence: 99%